IDENTIFICATION OF THE INTERACTION OF LITHIUM HEXAFLUOROPHOSPHATE SALT AND ETHYLENE CARBONATE (EC) SOLVENT IN LITHIUM ION BATTERY REDOX EVENTS USING CLASSICAL MOLECULAR DYNAMICS (MD) SIMULATION - Ngaderman, Hubertus; Sinaga, Ego Srivajawaty (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2024)
The aim of the research is to find the maximum velocity possessed by the molecules (Maxwell velocity distribution) of the solvation event of lithium hexafluorophosphate salt  interacting with ethylene carbonate (EC) solvent. We examined the electrolyte simulation of the reaction between lithium ions  and hexafluorophosphate  with ethylene carbonate (EC) solvent while the potential involved is the Lennard Jones potential. We use the epsilon (ε) and sigma (σ) parameters of Lennard Jones. These parameters are the independent variables used as a reference in determining the response variable which is the velocity of the molecules. Due to the large number of molecules involving the parameters and response variables per molecule mentioned above, we use a microcanonical assembly system (N, V, E) where the number of particles (N), system volume (V) and energy (E) are constant. The energy kT and the distance between molecules σ of 1 are inputted to the program in order to facilitate the computer in the simulation process. Solvation events where litium hexafluorophosphate  salt and solvent ethylene carbonate  interact then in the final positions of particles (equilibrium) the result is almost symmetry randomly in all planes. The velocity used is the most frequent velocity ( ) and is related to the kinetic energy.